High-Tech Counselor in the Digital Era: Integrating Information Technology into Modern Guidance and Counseling Practices - Halqim, Afanin; Rukiyati (LPPM Universitas Jambi, 2024)
In digital era, integrating information technology with guide and counselling services is crucial. This article looks at how information technology might improve the quality of counselling services, including accessibility and intervention efficacy. It takes a qualitative approach, based on a literature review, to investigate the possibilities, challenges, and best practices for using information technology into counselling. The findings demonstrated that information technology employed in guidance and counseling has the potential to increase the breadth of counselling services while also raising ethical, privacy, and counselor readiness concerns. The proposals include counselor training, the development of user-friendly technology, and legislation that promotes data privacy.